Oral steroids for resolution of otitis media with effusion in children (OSTRICH): a double-blinded, placebo-controlled randomised trial. Issue 10147 (18th August 2018) - Francis, Nick A; Cannings-John, Rebecca; Waldron, Cherry-Ann; Thomas-Jones, Emma; Winfield, Tom; Shepherd, Victoria; Harris, Debbie; Hood, Kerenza; Fitzsimmons, Deborah; Roberts, Amanda; Powell, Colin; Gal, Micaela; et al.
Summary: Background: Children with persistent hearing loss due to otitis media with effusion are commonly managed by surgical intervention. A safe, cheap, and effective medical treatment would enhance treatment options. Underpowered, poor-quality trials have found short-term benefit from oral steroids. We aimed to investigate whether a short course of oral steroids would achieve acceptable hearing in children with persistent otitis media with effusion and hearing loss. Methods: In this individually randomised, parallel, double-blinded, placebo-controlled trial we recruited children aged 2–8 years with symptoms attributable to otitis media with effusion for at least 3 months and with confirmed bilateral hearing loss. Participants were recruited from 20 ear, nose, and throat (ENT), paediatric audiology, and audiovestibular medicine outpatient departments in England and Wales. Participants were randomly allocated (1:1) to sequentially numbered identical prednisolone (oral steroid) or placebo packs by use of computer-generated random permuted block sizes stratified by site and child's age. The primary outcome was audiometry-confirmed acceptable hearing at 5 weeks. All analyses were by intention to treat. This trial is registered with the ISRCTN Registry, number ISRCTN49798431. Findings: Between March 20, 2014, and April 5, 2016, 1018 children were screened, of whom 389 were randomised. 200 were assigned to receive oral steroids and 189 to receive placebo. Hearing at 5 weeks was assessed in 183 children in the oral steroid group and in 180 in the placebo group. Acceptable hearing was observed in 73 (40%) children in the oral steroid group and in 59 (33%) in the placebo group (absolute difference 7% [95% CI −3 to 17], number needed to treat 14; adjusted odds ratio 1·36 [95% CI 0·88–2·11]; p=0·16). There was no evidence of any significant differences in adverse events or quality-of-life measures between the groups. Interpretation: Otitis media with effusion in children with documented hearing loss and attributable symptoms for at least 3 months has a high rate of spontaneous resolution. A short course of oral prednisolone is not an effective treatment for most children aged 2–8 years with persistent otitis media with effusion, but is well tolerated. One in 14 children might achieve improved hearing but not quality of life. Discussions about watchful waiting and other interventions will be supported by this evidence. Funding: National Institute for Health Research (NIHR) Health Technology Assessment programme.